Measurement of transpiration in citrus rootstocks - Castro, Paulo R. C.; Banzatto, David A.; Donadio, Luiz C. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
Diurnal transpiration rates of four citrus rootstocks were measured during 12 hours separated by intervals of 60 minutes, through the weighing method. Plants of Poncirus trifoliata, Citrus aurantium, Citrus sinensis, and Citrus limonia do not present statistical differences in the daily march of transpiration. In the studied conditions C. limonia showed higher leaf area than P. trifoliata, C. aurantium, and C. sinensis. There was a positive correlation between leaf area and transpiration of the four citrus rootstodks.